Visceral hypersensitivity and diagnostic markers in functional gastrointestinal disorders: expert opinion - Mehrotra, Puneet (International Journal of Advances in Medicine, 2024)
Functional gastrointestinal disorders (FGIDs), including irritable bowel syndrome (IBS), present diagnostic challenges due to the absence of specific biomarkers and reliance on symptom-based criteria like the Rome IV classification. IBS, characterized by abdominal discomfort, irregular bowel habits and bloating, affects up to 21% of populations globally, with varying prevalence across regions. Visceral hypersensitivity (VH) is a hallmark of IBS, particularly in diarrhea-predominant IBS (IBS-D), contributing to enhanced pain perception and gut dysmotility. VH involves complex mechanisms integrating peripheral and central nervous system pathways, affecting pain processing and emotional responses. Diagnostic approaches for IBS are hindered by overlapping symptoms with other gastrointestinal disorders and the dynamic nature of gut microbiota. Biomarkers, such as serum and fecal panels, gene expression profiles and psychological assessments, aim to enhance diagnostic accuracy and differentiate IBS subtypes. These biomarkers, including fecal calprotectin, short-chain fatty acids (SCFA), volatile organic compounds (VOCs) in breath tests and specific antibodies against microbial toxins, offer insights into the pathophysiology of IBS and aid in subtype prediction. Considering the scarcity of information on intricacies of VH in IBS and need gap in understanding the precise diagnostic markers for IBS, three physical focus group meetings were conducted with 25 expert gastroenterologists across India. Existing evidence and clinical experience with respect to the diagnosis of IBS, concept of visceral hypersensitivity and its importance in managing IBS, current treatment modalities and the role of various diagnostic biomarkers were discussed in detail by the experts and expert opinions were consolidated and finalized after approval by all participants.